Fundamental Objectives and Directive Principles of State Policy in the Nigerian Constitution: Re-Examining the Non-Justiciability of Socio-Economic Rights - Babafemi Odunsi; Ogbole Ogancha O; Oreoluwa Omotayo Oduniyi (CV. Pustaka Parawali, 2025)
This study examines the projections and weaknesses in realising the socio-economic rights enshrined in Chapter II of the 1999 Constitution of the Federal Republic of Nigeria (as amended). It also elaborates on the main objectives and directives of the state policy. This study explicitly examines each objective and directive principle, as well as how they are designed to improve the quality of governance based on social and economic rights. This study uses a doctrinal legal method with a conceptual, statute, and case law approach. A key finding of this study is that these constitutional provisions, although not legally enforceable, can be applied under clear and defined parameters. These important limitations are explained in detail in the 1999 Constitution. This is mainly due to current efforts in other jurisdictions with similar provisions that support the enforcement and applicability of such constitutional provisions to strengthen and promote socio-economic rights. This study also identifies challenges that hinder the enforcement of Chapter II of the Constitution, mainly related to efforts to realise social and economic rights in the administration of government in Nigeria. This study concludes by providing reasonable recommendations to make this constitutional objective enforceable in court and achievable, as applied in other jurisdictions. Thus, the contribution of this study is how the government, through its legal institutions, can guarantee the enforcement of social and economic rights for every citizen in Nigeria.